2020
DOI: 10.22317/jcms.v6i2.748
|View full text |Cite
|
Sign up to set email alerts
|

Tumor of Misinformation Consumption and Sharing among People in Coronavirus (Covid-19) Crisis; a Commentary

Abstract: This is a commentary article, so it does not abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…There is a proposal to include health preventive measures into elementary and high school curricula. 34 It has been reported that the promotion of health literacy in schools resulted in enhanced basic cancer literacy among middle and high school students. 35 Health agencies have been urged to have a more proactive and agile public health presence on social media and to combat the spread of fake news by directly responding to fake news and by building disease detection and surveillance systems through social media and unusual activity monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a proposal to include health preventive measures into elementary and high school curricula. 34 It has been reported that the promotion of health literacy in schools resulted in enhanced basic cancer literacy among middle and high school students. 35 Health agencies have been urged to have a more proactive and agile public health presence on social media and to combat the spread of fake news by directly responding to fake news and by building disease detection and surveillance systems through social media and unusual activity monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…There is a proposal to include health preventive measures into elementary and high school curricula. 34 It has been reported that the promotion of health literacy in schools resulted in enhanced basic cancer literacy among middle and high school students. 35 …”
Section: Introductionmentioning
confidence: 99%
“…However, in the age of multiple information sources and diverse communication channels users do not always access the most valid information. It is estimated that there are 11 different types of information sources ranging from valid information to untrusted or doubtful information (Ashrafi‐Rizi & Kazempour, 2020). Experts in the field of infectious diseases suggest that during a pandemic virtual communication provides a good way to inform patients who are in isolation wards (Hollander & Carr, 2020).…”
Section: Introduction: Information Needs During a Pandemicmentioning
confidence: 99%
“…The proliferation of internet-based health news encourages the referencing of media and academic articles, which may exaggerate the strength of results and mislead the public [ 32 ]. Contradictory, doubtful (untrustworthy), false, or misleading information may lead to public panic and, in turn, cause mental health symptoms [ 33 ]. These untrusted media sources heighten confusion and fearmongering [ 8 , 32 ] and cause anxiety and panic among students.…”
Section: Introductionmentioning
confidence: 99%